A Mixed-Criticality Task Scheduling Method Based on Comprehensive Impact Factor. (January 2023) - Tiansen, Li; Shujuan, Huang; Feng, Xiao; Wenjuan, Zhang; Xingxing, Han
Abstract: We propose a mixed-criticality task scheduling method based on the comprehensive impact factor to improve the proportion of scheduling for low-criticality tasks when the system critical level is switched. Specifically, we first consider the critical level, task utilization, and idle window of each task under different critical levels (high or low) to determine the comprehensive impact factor and use it as a priority indicator for task execution. Then, we sort the tasks according to the priority order and add them to the ready queue to be scheduled. Finally, in the execution phase, if a critical level switch occurs, we do not directly discard the low-criticality tasks, but keep them and schedule them for after the high-criticality tasks are completed. Experimental results show that this method improves the schedulability of low-criticality tasks by approximately 10% compared to the Earliest Deadline First with Dual Virtual Deadlines (EDF-DVD) and the Forward and Backward Time Window Partition-Criticality Factor Prior (FBTWP-CFP) algorithms, and reduces the preemption and migration ratio of tasks by approximately 17.9%.